IMPROVING THE COMPETENCE OF WRITING QUALITY SCIENTIFIC PAPERS FOR EDUCATORS AND ASPIRING ACADEMICS - Suparno; Sebayang, Karuniana Dianta A.; Dila Lestari, Fitra; Riswandi; Maulida, Ervina (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2025)
Enhancing the competency of scientific writing for educators and future academics has become an urgent necessity in facing global academic challenges. The low number of quality publications and the minimal understanding of international publication standards often hinder academic capacity development. Therefore, this International Collaborative Community Service Program (PPM-KI) aims to equip educators and future academics with scientific writing skills that comply with the standards of reputable national and international journals. Furthermore, this program also encourages cross-country academic collaboration in the production and publication of scientific works, thereby increasing academic recognition and strengthening global scientific networks. Through this program, several targeted outcomes include the publication of articles in ISSN-registered journals or ISBN/ISSN-registered national seminar proceedings, the publication of articles in mass media or online academic platforms, and video documentation of activities uploaded to the LPPM YouTube channel. Additionally, the program also targets the active involvement of students in community service activities and the acquisition of recognition letters from international partners as proof of their enhanced academic capacity. Evidence of collaborative partnership in the form of an Implementation of Arrangement (IA) is also a key outcome, demonstrating the program's success in building international networks. With this program, it is expected that educators and future academics will improve the quality and quantity of their scientific publications, thus contributing to strengthening a more competitive academic ecosystem at the international level. Moreover, the program's success will also support the achievement of key performance indicators for higher education institutions and contribute to academic development based on global collaboration